2014
DOI: 10.1016/j.jconrel.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial drug distribution generated from local epicardial application: Potential impact of cardiac capillary perfusion in a swine model using epinephrine

Abstract: Prior studies in small mammals have shown that local epicardial application of inotropic compounds drives myocardial contractility without systemic side effects. Myocardial capillary blood flow, however, may be more significant in larger species than in small animals. We hypothesized that bulk perfusion in capillary beds of the large mammalian heart enhances drug distribution after local release, but also clears more drug from the tissue target than in small animals. Epicardial (EC) drug releasing systems were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The disposition within the cardiac wall follows the assumed pattern after a postmortem study by Garcia et al 175859. Therefore, investigating the disposition between cardiac mural layers requires more mechanistic insight, most likely with a permeability-limited kinetics assumption.…”
Section: Discussionmentioning
confidence: 90%
“…The disposition within the cardiac wall follows the assumed pattern after a postmortem study by Garcia et al 175859. Therefore, investigating the disposition between cardiac mural layers requires more mechanistic insight, most likely with a permeability-limited kinetics assumption.…”
Section: Discussionmentioning
confidence: 90%
“…However, larger increases in the surface area had a more pronounced effect on increasing the concentration of drug analog along the transmural thickness at shorter time scales. Factors such as the size and thickness [5] of the heart tissue and the size of the infarct may need to be considered when determining the surface area of the device, and when scaling up.…”
Section: Discussionmentioning
confidence: 99%
“…In one exemplary configuration of this strategy, a biomaterial loaded with therapeutic agents acts as a reservoir on the surface of the heart, providing sustained release to a localized region, thereby preventing adverse systemic affects and increasing myocardial uptake [1] . A wide variety of therapeutics ranging from small molecules such as amiodarone [4] , epinephrine [5] , dobutamine [6] to larger biomolecules such as peptides [7] , growth factors [3] , exosomes [8] , cells [9], [10], [11], [12], [13] , and gene therapies [14] preloaded onto biomaterials and implanted on the epicardial surface have been investigated in animal models of a range cardiovascular conditions. Enhanced therapeutic benefit relative to the more standard methods of delivery has been shown in these studies, demonstrating that the epicardial strategy may accelerate clinical translation of these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Lovich and colleagues demonstrated that epicardial delivery leads to rapid diffusion of drugs throughout the myocardium, with 500x increase in potency compared to systemic delivery. 39,40 Whyte and colleagues recently reported the utility of pericardial MSC delivery to improve cardiac function over a 4 week period. 13 This innovative strategy, however, required weekly cellular injection into the epicardial reservoir to achieve efficacy.…”
Section: Therapeutic Efficacy Of Encapsulated Mscs In Ischemic Ratsmentioning
confidence: 99%